The Principles of Sustainable Economics in Islamic Civilization: A Historical Study - Inayati, Anindya Aryu; Ariyanti, Lita Dwi; Kamal, Nurul Ummatun; Miliana, Afina Fahru (Jurnal Studi Islam Indonesia (JSII), 2025)
The green economy program is one of the flagship programs rolled out by the Indonesian government and global countries, in order to realize sustainable world development. The concept of green economy or sustainable economy that prioritizes environmentally friendly economic activities is actually not new in Islamic civilization. This research aims to describe the principles and practices of sustainable economics in Islamic civilization. The method used in this study is a literature method using a historical approach and descriptive data analysis. The results of the study show that the principle of sustainable economy in Islamic civilization is based on the basic principle of muamalah, namely justice and the achievement of maslahah. The sustainable economic practice during the Islamic civilization was carried out by integrating human obligations as khalifatullah fil 'ardh. Islamic economic activities prioritize the protection of animals and the environment, revive dead land, and prioritize the common good.